2016
DOI: 10.1002/prca.201500139
|View full text |Cite
|
Sign up to set email alerts
|

Protein translation occurs in platelet concentrates despite riboflavin/UV light pathogen inactivation treatment

Abstract: This study demonstrates for the first time that platelets can synthesize proteins despite the riboflavin and UV treatment and suggests that platelets may possess a mechanism to protect their mRNA from damage by the PI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…This level of peptide overlap between two independent experiments lies in the range of technical replicates showing 35% to 60% repeatability and is additionally impacted by the donor‐to‐donor variability. To detect biologically significant alterations, we applied selection criteria of a fold change of protein level of either less than 0.5 or more than 1.5 . There were no marked membrane protein changes over storage in RBC Ctrl .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of peptide overlap between two independent experiments lies in the range of technical replicates showing 35% to 60% repeatability and is additionally impacted by the donor‐to‐donor variability. To detect biologically significant alterations, we applied selection criteria of a fold change of protein level of either less than 0.5 or more than 1.5 . There were no marked membrane protein changes over storage in RBC Ctrl .…”
Section: Resultsmentioning
confidence: 99%
“…To detect biologically significant alterations, we applied selection criteria of a fold change of protein level of either less than 0.5 or more than 1.5. 32 There were no marked membrane protein changes over storage in RBC Ctrl . While alterations appeared variable and inconsistent for RBC HH over storage (RBC HH Days 5 and 42), RBC HH displayed a number of reproducible protein changes with respect to RBC Ctrl at baseline ( Table 2).…”
Section: Proteomic Analysis Of Rbc Hh and Rbc Ctrl Ghost Fractions Dumentioning
confidence: 89%
“…The increase in abundance of α‐tubulin in the urea‐soluble fraction of refrigerated PLTs was considerable and cannot be accounted for solely by protein migration from the cytosol. Previous studies have demonstrated that PLTs contain the necessary machinery for de novo protein synthesis, which can be activated by storage at room temperature and the use of pathogen inactivation systems . Thus, it is plausible that refrigeration may also trigger the activation of de novo protein synthesis facilitating α‐tubulin production, although further studies are required to demonstrate this.…”
Section: Discussionmentioning
confidence: 99%
“…PITs have also been found to exacerbate platelet storage lesions [37]. Even though platelets are enucleated cells, the platelets remain capable of synthesizing some proteins [36,38,39,40]. Indeed, much attention has been focused on the platelet proteome, which involves more than 4000 proteins to date [41], in order to better define the impact of PITs on platelet function.…”
Section: Alterations and Oxidation Of Platelet Proteinsmentioning
confidence: 99%